0441 Exposure to dinitroanilines and risk of lung cancer (lc) by subtypes: results from the agrican cohort. (21st August 2017) - Boulanger, Mathilde; Tual, Séverine; Lemarchand, Clémentine; Baldi, Isabelle; Clin, Bénédicte; Lebailly, Pierre
Abstract : Introduction: 2, 6-Dinitroanilines included 15 herbicides, some of which are still used on a wide range of crops worldwide and in France, especially pendimethalin which was given special attention by the IARC. The aim of our analyses was to estimate the associations between LC and exposure to pendimethalin, benfluralin, butralin, ethalfluralin, nitralin, oryzalin, trifluralin -all once or still authorised in France-, in the French AGRIculture and CANcer (AGRICAN) cohort. Methods: More than 1 80 000 people affiliated for at least 3 years to the agricultural health insurance scheme were enrolled between 2005 and 2007. A total of 563 incident LC were identified from enrollment to 2011. Data on crop exposure during lifetime (13 crops, specific tasks including pesticide use) were collected. The evaluation of potential exposure to each dinitroaniline relied on a specific crop-exposure matrix, PESTIMAT. Analyses were adjusted on smoking history, involvement in cattle and horse breeding, peas growing, exposure to farming activities during childhood. Results: In the population, 16 533 people (11.2% of the cohort) were potentially exposed to one or more dinitroanillines. Pendimethalin and trifluralin were the most frequently used, but not associated to any increased risk of LC, nor was exposure to dinitroanillines in general. We observed an increased risk of adenocarcinoma for oryzalin exposure (HR=2.93[1.13–7.59], n=5 exposed cases), but with no linear effect with duration. Conclusion: We did not found any increased risk of LC among pendimethalin users. Our results suggest a possible association of lung adenocarcinoma with oryzalin, currently authorised in France, especially on the vineyard.